Journal of low power electronics and applications (MDPI Publishing, 2011)
"Journal of Low Power Electronics and Applications (ISSN 2079-9268) is an open access journal which provides an advanced forum for the studies of electronics for low power applications. A special emphasi[s] is made on ultralow power bio-medical applications. It publishes reviews, regular research papers and short communications."
Keywords: Power electronics : Periodicals; Low voltage systems : Periodicals; Bioelectronics : Periodicals; Medical electronics : Periodicals; Bioelectronics; Low voltage systems; Medical electronics; Power electronics; Biomedical Engineering